How Dangerous? Substance Use Risk Perceptions in Chilean Preadolescents - Sable, Leba; Vidal, Jessica; Estrada-Goic, Claudia; Carcamo, Rodrigo A. (My University, 2025)
Early substance use initiation among children represents a significant risk to public health. Research suggests that early positive perceptions and cognitions of elementary students toward substance use may predict later use during adolescence. Studies among adolescent populations have shown an inverse relationship between substance use and risk perceptions. To gain insight into alcohol, tobacco, and marijuana risk perceptions prior to adolescence, we analyzed data from the Chilean Early Childhood Longitudinal Survey (ELPI). In a sample of 5,278 families (mean age of preadolescents 10.63 years, SD = .64; 50.5% males), our findings showed that an important proportion of Chilean 10 years old did not perceive occasional tobacco, alcohol, or marijuana use to be high-risk activities. However, the majority of respondents did consider daily substance use to be a high-risk activity, with some variation across substances. Overall, older preadolescents were more likely to consider substance use to be less risky compared to their slightly younger counterparts. Our analysis also demonstrated that past month substances use by caregivers were all found to be predictive of low-medium risk perceptions among preadolescents surveyed, while conversely, caregivers' negative reactions to finding out their child had used a substance decreased the likelihood of holding low-medium risk perceptions. Individuals from single-parent households were less likely to consider substance use as being high-risk compared to their peers. Preadolescents with caregivers reporting higher average incomes were also more likely to hold lower risk perceptions of occasional substance use. Implications for public policies to prevent substance use in the pre-adolescent population are discussed.
Keywords: preadolescent; risk perceptions; substance use